Advanced Computing and Systems for Security Volume Seven - Chaki, Rituparna; Cortesi, Agostino; Saeed, Khalid; Chaki, Nabendu (Advances in Intelligent Systems and Computing, 2019)
X, 171 p. 63 illus., 37 illus. in color.